Nonlinear refractive index measurements in antimony-sulfide glass films using a single beam nonlinear image technique - de Araujo, C. B.; Boudebs, G.; Briois, V; Pradel, A.; Messaddeq, Younes [UNESP]; Nalin, Marcelo [UNESP] (Elsevier B.V., 2006)
The nonlinear refractive index, n(2), of films based on the new glass system Sb(2)O(3)-Sb(2)S(3) was measured at 1064 nm with laser pulses of 15 ps, using a single-beam nonlinear image technique in presence of a phase object. The films were prepared from bulk glasses by RF-sputtering. A large value of n(2) = 3 x 10-(15) m(2)/W, which is three orders of magnitude larger than for CS(2), was determined. The result shows the strong potential of antimony-sulfide glass films for integrated nonlinear optics. (c) 2005 Elsevier B.V. All rights reserved.